Aqueous dispersions of nanobubbles: Generation, properties and features. (August 2016) - Azevedo, A.; Etchepare, R.; Calgaroto, S.; Rubio, J.
Graphical abstract: Highlights: A new way to generate nanobubbles (NBs) (>10 9 NBs mL −1 ) was invented. NBs were stable (same concentration) for at least two weeks. The NBs concentration is a function of water/air saturation pressure and surface tension. NBs strongly adhered onto pyrite surface allowing bubbles attachment. The use of NBs will lead to cleaner and more efficient mineral flotation. Abstract: Nanobubbles (NBs) have interesting and peculiar properties such as high stability, longevity and high surface area per volume, leading to important applications in mining-metallurgy and environmental areas. NBs are also of interest in interfacial phenomena studies involving long-range hydrophobic attraction, microfluidics, and adsorption at hydrophobic surfaces. However, little data are available on effective generation of concentrated NBs water dispersions and on their physicochemical and interfacial properties. In this work, air was dissolved into water at pH 7 and different pressures, and a flow was depressurized through a needle valve to generate 150–200 nm (mean diameter) NBs and MBs-microbubbles (about 70 μm). Microphotographs of the NBs were taken only in the presence of blue methylene dye as the contrast medium. Main results showed that a high concentration of NBs (number per volume) was obtained by decreasing the saturation pressure and surface tension. The number of NBs, at 2.5 bar, increased from 1.0 × 10 8 NB mL −1 at 72.5 mN m −1 to 1.6 × 10 9 NB mL −1 at 49 mN m −1 (100 mg L −1 α-Terpineol). The NBs mean diameter and concentration only slightly varied within 14 days, which demonstrates the high stability of these highly concentrated NBs aqueous dispersions. Finally, after the NBs were attached to the surface of a grain of pyrite (fairly hydrophobic mineral), the NBs dramatically increased the population of MBs, which shows the enhancement of particle hydrophobicity due to NBs adhesion. The results were explained in terms of interfacial phenomena and it is believed that these tiny bubbles, dispersed in water at high concentrations, will lead to cleaner and more sustainable mineral flotation.